FAKTOR – FAKTOR INTERNAL YANG MEMPENGARUHI MINAT DAN MOTIVASI MAHASISWA SEMESTER IV PRODI ILMU KEPERAWATAN DALAM PRAKTIK MANDIRI DI LABORATORIUM KEPERAWATAN STIKES WIRA HUSADA YOGYAKARTA TAHUN AKADEMIK 2011/2012 - Marsiyah Marsiyah; Titih Huriah; Tri Winarni (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2014)
ABSTRACTBackground: A Practical Learning Experience (PBP) was a leaning process to prepare students to conduct a clinical learning. PBP enforcement was divided into three session namely: guided, independent and skill evaluation. An independent session was an independent laboratory practice due to the students had their own initiatives to conduct a practical learning. There were factors that could influence students in learning one of them was most significant factor that influenced student learning namely learning interestand motivation. In this research it was obtained eternal factors of students’ interest and motivation towards independent practice in nursing laboratory.Objective: to know the external factors that influenced interest and motivation of 4  Semester S-1 NursingStudy Program to conduct an independent practice in Nursing Laboratory of STIKES Wira Husada Yogyakarta.Method: this was a quantitative non-experimental research using a descriptive analytical method with a cross sectional approach. Sample taking used a proportional random sampling technique with 91respondents. Data collection technique was by distributing questionnaire and then research result data was processed using a statistical non parametric and a Spearman Rank correlation formula.Result: the students evaluated school factors: lecturers teaching method who had  high category of 87.9%, curriculum had high category of 83.5%, lecturer-student relationship had high category of 79.1%, student-student relationship had high category of 85.7%, facilities had high category of 49.5%, school term had high category of 71.4%. An environmental condition factor had high category (61.5%), and lecturer efforts factor to make their students learning had high category (75.2%). Conclusion: there were external factors that influenced interest and motivation of 4th  Semester S-1 Nursing Study Program to learn an independent practice in Nursing Laboratory of STIKES Wira Husada Yogyakarta.